Kemapanan dan daya saing pajak gadai Islam di Malaysia perspektif perintis - Abdul Razak Azila, Muhammad Fidlizan, Mohd Hussin Mohd Yahya, Abdul Hadi Fatimah Salwa, (N/A, 2014)
Kemapanan dan daya saing pajak gadai Islam di Malaysia perspektif perintis by Abdul Razak Azila, Muhammad Fidlizan, Mohd Hussin Mohd Yahya, Abdul Hadi Fatimah Salwa,